Single-cell nuclear RNA-sequencing reveals dynamic changes in breast muscle cells during the embryonic development of Ding’an goose - Tieshan Xu; Yingxiu Hu; Haokai Fan; Xinli Zheng; Qicheng Jiang; Lizhi Lu; Jie Li; Zhemin Lin; Lihong Gu (PLoS ONE, 2025)
Breast muscle is a crucial trait in poultry meat production. Previous studies have identified embryonic day 15 (E15), E21, and E31 as key time points in the breast muscle development of Ding’an goose, yet the specific molecular mechanisms remain unclear. In this study, we analyzed cellular heterogeneity and molecular dynamics at 15th day of embryonic breast muscle of Dingan goose (E15), E21, and E31 by using single-nucleus RNA-sequencing (snRNA-seq) technology. Nine types of cells were discovered, including fibroblast adipogenic progenitor cells (FAPs), myocytes and muscle stem cells (MuSCs), with notable differences among the three developmental stages in terms of cell type and abundance: FAPs and MuSCs gradually decreased from 42.3% and 35.6% (E15) to 15.7% and 12.2% (E31), respectively, while myocytes increased from 18.5% (E15) to 70.1% (E31). Additionally, the distinct heterogeneity of myocytes, MuSCs and FAPs was determined based on the analysis of gene regulatory networks for each cluster. Developmental trajectory analysis identified genes related to the function and development of MuSCs. The identified differentially expressed genes elucidate the molecular mechanisms of cellular dynamic changes during breast muscle development. This study generated a nuclear profile for single muscle cells that played a key role in the development of breast muscle in Ding’an goose embryos. We investigated metabolic changes at the cellular level during three key developmental stages, thereby refining our understanding of the molecular mechanisms underlying pectoral muscle development specifically in embryonic Ding’an goose.